Dysmenorrhea, endometriosis, adenomyosis: clinical and pathogenetic relationships - A L Unanian; I S Sidorova; A D Nikonets; Yu V Kostina; N N Kuzenkova; A M Elisavetskaia; D V Baburin (IP Berlin A.V., 2018)
This publication is devoted to the most common problem in women of reproductive age - dysmenorrhea. Unfortunately, the underestimation of the importance of dysmenorrhea often occurs on the part of both patients and doctors. Meanwhile, dysmenorrhea causes not only a decrease in the quality of life, but also a number of serious disorders, including the risk of developing endometriosis, adenomyosis and even tumorous diseases. With such articles as prevention and prevention of diseases.